The rise of the London money market, 1640-1826 - Bisschop, W. R. (London : Cass, 1968)
This author gives a most careful description of the history of the Bank of England, only in its relation to the state.
Translation of De opkomst der Londensche geldmarkt, 1640-1826.
Originally published 1896. This translation originally published 1910.
Bibliography: p. 17-21.
osc 24/07/2018
Loans
Keywords: Banks and banking